Computer organization and design : the hardware/software interface - Patterson, David A. (Elsevier/Morgan Kaufmann, Morgan Kaufmann is an imprint of Elsevier, 2016)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher.